AL-AḌDĀD (KONTRANIM) DAN IMPLIKASINYA DALAM PERBEDAAN TAFSIR - Azam Bahtiar (Tanzil: Jurnal Studi Al-Quran, 2021)
This paper tries to prove that differences in interpretation of the Al-Qur’an are necessary and inevitable. Even if it we can assume that the reading of the text can be free from ideological intervention and the tendency of commentators, differences in interpretation will still exist. To prove it, the author proposes and examines a linguistic phenomenon known as al-aḍdād or contranym. Using a number of muktabar and standard traditional commentaries, this paper examines six contranym entries that appear in the text of the Al-Qur’an, and shows their implications for differences in interpretation—both differences called tanawwu'ī (variative) and taḍādd (contradictory).